ALASAN MASUK DAN ALASAN MEMILIH PROGRAM STUDI ANTARA ALUMNI DI UNIVERSITAS TERBUKA - Listyarini, Sri; Ratnawati, Tina; Prayekti, Prayekti; Milwan, Milwan (Jurnal Pendidikan Terbuka Dan Jarak Jauh, 2012)
Universitas Terbuka (UT) as an open and distance higher education institution needs to have data on the student reasons why they enrolling at UT and why they choose their study programs. The data can be obtained from alumni who recently graduated, for that UT has developed an exit survey applications. There are two programs that are managed by UT, the Regular Program or Non-Pendas and Basic Education Program (Pendas). In this study respondents of the exit survey consist of 3,190 Regular Program alumni and 34,856 Program Pendas alumni, which is a graduate of UT during 2009.2 to 2010.2 semesters. The results of exit survey data processing shows that there are some differences regarding the reasons for the UT enrollment and reasons for choosing study program, among the Regular and Pendas Program alumni. The main reason for the Regular and Pendas Program alumni enrolled at UT is "Knowledge Improvement". While the main reason for choosing study program for the Regular Programme alumni is "Supporting the Job", while alumni from Pendas Program is "Knowledge Improvement". In the future the data obtained from exit survey can be used for dissemination and promotion, increasing the number of students, as well as reducing the number of non-active students. Universitas Terbuka (UT) sebagai institusi pendidikan tinggi terbuka jarak jauh perlu memiliki data mengenai apa alasan mahasiswa masuk UT dan apa alasan mereka memilih program studi. Data tersebut dapat diperoleh dari alumni yang baru saja lulus, untuk itu UT telah mengembangkan aplikasi exit survey. Ada dua program yang dikelola oleh UT, yaitu Program Reguler atau Non-Pendas dan Program Pendidikan Dasar (Pendas). Dalam penelitian ini responden exit survey dari Program Reguler sebanyak 3.190 dan Program Pendas berjumlah 34.856, yang merupakan lulusan UT pada masa yudisium 2009.2 sampai dengan 2010.2. Hasil pengolahan data exit survey memperlihatkan bahwa terdapat beberapa perbedaan mengenai alasan masuk UT dan alasan memilih program studi, antara alumni Program Reguler dan Pendas. Alasan utama masuk UT bagi alumni Program Reguler maupun Pendas adalah Menambah Pengetahuan. Sedangkan alasan utama memilih program studi bagi alumni Program Reguler adalah Menunjang Pekerjaan, sementara alumni Program Pendas adalah Menambah Pengetahuan. Di masa yang akan datang data yang diperoleh dari exit survey dapat digunakan untuk sosialisasi dan promosi, meningkatkan jumlah mahasiswa, serta menurunkan jumlah mahasiswa non-aktif.